Does prolonged prone position affect intracranial pressure? prospective observational study employing Optic nerve sheath diameter measurements - Ufuk Demir; Öztürk Taşkın; Ayşe Yılmaz; Soylu, Veysel G.; Zahide Doğanay (Springer Science and Business Media LLC, 2023)
Abstract Background Our aim in this observational prospective study is to determine whether the prone position has an effect on intracranial pressure, by performing ultrasound-guided ONSD (Optic Nerve Sheath Diameter) measurements in patients with acute respiratory distress syndrome (ARDS) ventilated in the prone position. Methods Patients hospitalized in the intensive care unit with a diagnosis of ARDS who were placed in the prone position for 24 h during their treatment were included in the study. Standardized sedation and neuromuscular blockade were applied to all patients in the prone position. Mechanical ventilation settings were standardized. Demographic data and patients’ pCO2, pO2, PaO2/FiO2, SpO2, right and left ONSD data, and complications were recorded at certain times over 24 h. Results The evaluation of 24-hour prone-position data of patients with ARDS showed no significant increase in ONSD. There was no significant difference in pCO2 values either. PaO2/FiO2 and pO2 values demonstrated significant cumulative increases at all times. Post-prone SPO2 values at the 8th hour and later were significantly higher when compared to baseline (p < 0.001). Conclusion As a result of this study, it appears that the prone position does not increase intracranial pressure during the first 24 h and can be safely utilized, given the administration of appropriate sedation, neuromuscular blockade, and mechanical ventilation strategy. ONSD measurements may increase the safety of monitoring in patients ventilated in the prone position.
Keywords: Respiratory Distress Syndrome; Intracranial Pressure; Intracranial pressure; Research; Neuroimaging; Optic Nerve; Intracranial pressure monitoring; Prone position; Anesthesiology; Optic nerve sheath diameter; Prone Position; Humans; ARDS; RD78.3-87.3; Prospective Studies; Intracranial Hypertension; Ultrasonography; 3. Good health